Characterizing disease progression of nonalcoholic steatohepatitis in Leptin-deficient rats by integrated transcriptome analysis. Issue 6 (March 2021) - Lu, Ping; Yang, Guang; Jiang, Lichun; He, Wen; Wu, Wanwan; Qi, Lingbin; Shen, Shijun; Rao, Junhua; Zhang, Peng; Xue, Zhigang; Jiang, Cizhong; Fan, Guoping; et al.
Nonalcoholic steatohepatitis (NASH) is an aggressive liver disease threatening human health, yet no medicine is developed to treat this disease. In this study, we first discovered that Leptin mutant rats ( Lep ΔI14/ΔI14 ) exhibit characteristic NASH phenotypes including steatosis, lymphocyte infiltration, and ballooning after postnatal week 16. We then examined NASH progression by performing an integrated analysis of hepatic transcriptome in Leptin -deficient rats from postnatal 4 to 48 weeks. Initially, simple steatosis in Lep ΔI14/ΔI14 rats were observed with increased expression of the genes encoding for rate-limiting enzymes in lipid metabolism such as acetyl-CoA carboxylase and fatty acid synthase. When NASH phenotypes became well developed at postnatal week 16, we found gene expression changes in insulin resistance, inflammation, reactive oxygen species and endoplasmic reticulum stress. As NASH phenotypes further progressed with age, we observed elevated expression of cytokines and chemokines including C-C motif chemokine ligand 2, tumor necrosis factor ɑ, interleukin-6, and interleukin-1β together with activation of the c-Jun N-terminal kinase and nuclear factor-κB pathways. Histologically, livers in Lep ΔI14/ΔI14 rats exhibited increased cell infiltration of MPO + neutrophils, CD8 + T cells, CD68 + hepatic macrophages, and CCR2 + inflammatory monocyte-derived macrophages associated with macrophage polarization from M2 to M1. Subsequent cross-species comparison of transcriptomes in human, rat, and mouse NASH models indicated that Leptin -deficient rats bear more similarities to human NASH patients than previously established mouse NASH models. Taken together, our study suggests that Lep ΔI14/ΔI14 rats are a valuable pre-clinical rodent model to evaluate NASH drug safety and efficacy.